Development of Caring Model for Pregnant Women with Iron Deficiency Anemia at Public Hospital in District Nathawi , Songkhla: Development of Caring Model for Pregnant Women with Iron Deficiency Anemia at Public Hospital in District Nathawi , Songkhla - Channuan, Thanwarat; Singsri, Thidarat; Nawsuwan, Kittiporn (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Maternal iron-deficiency anemia arising from physiological changes, combined with inappropriate self-care behaviors among pregnant women, adversely affects both mother and fetus. This study aims to examine the situation and problems, identify success factors, develop a model, and evaluate the effectiveness of a care model for pregnant women with iron-deficiency anemia in public health service facilities in Na Thawi District, Songkhla Province. Methods This is a research and development (R&D) study conducted in three phases: Phase 1: Situation and problem analysis and success factors. Document analysis and qualitative data collection from 18 practicing nurses. Phase 2: Model development, validated by 3 experts (content validity index, CVI = 1.00). Phase 3: Evaluation of the model’s effectiveness using a one-group pretest–posttest quasi-experimental design with 18 practicing nurses and 33 pregnant women. Data were analyzed using descriptive statistics and a paired (dependent) t-test. Results Data from fiscal years 2022–2023 show an increasing trend of anemia among pregnant women, with issues including delayed prenatal care, non-adherence to iron supplements, and low participation in self-care. Key success factors identified were knowledge and awareness, dietary behavior, and community involvement. The developed model, named the NAVIE Model, comprises: N: Nursing roles A: Aims of individual pregnant women V: Village health volunteers’ buddy (Aso Ministry volunteer buddy) I: Information technology E: Engaged family. After implementing the NAVIE model, pregnant women showed a statistically significant increase in hemoglobin concentration (Hb) and knowledge (p < .001). Satisfaction levels of both professional nurses and pregnant women were very high (Mean = 4.83, SD = 0.38 for nurses; Mean = 4.82, SD = 0.39 for pregnant women). Conclusion and Recommendations The NAVIE model should be expanded to non-communicable diseases and child development promotion activities. Additionally, the capacity of professional nurses in caring for pregnant women should be enhanced, with strengthened interprofessional collaboration.